Portraits of Linguists A Biographical Source Book for the History of Western Linguistics, 1746-1963 - Sebeok, Thomas A. (Indiana University Press, 1966)
The main events in the history of linguistics from the late eighteenth century to the present are here presented by means of a unique method. The thought and ideas of distinguished linguists are cosidered in biographical accounts by other well-known scholars in the field. Wherever possible, the life of each linguist is discussed by his own pupil, so that a natural continuity of ideas occurs. Thus the reader is able to trace the intellectual transmission, growth, and development of particular schools of linguistic thought. Among the American and European linguists, included are Sir William Jones, Wilhelm von Humboldt, Jacob Grimm, W. D. Whitney, Ferdinand de Saussure, Edward Sapir, Nikolaj Trubetzkoy, Franz Boas, Leonard Bloomfield, and Leo Spitzer.